Prevalence and Predictors of Restrictive Lung Dysfunction among Patients with Type 2 Diabetes Mellitus - Sumayya Shabbir; Ghulam Abbas; Asad Manzoor; Gull Afshan Razi; Roozina Shaikh; Ramla Ata (International Journal of Pharmacy Research & Technology (IJPRT), 2026)
Objective: Type 2 Diabetes Mellitus (T2DM) is a systemic disease, and the lungs are a target organ of the disease. This study was aimed to find out the prevalence of Restrictive Lung Dysfunction (RLD) in T2DM patients and to identify its independent clinical and biochemical predictors. Material and Methods: A cross-sectional observational study of 450 adult patients of T2DM attending a tertiary care endocrinology clinic was conducted. The definition of RLD was a Forced Vital Capacity (FVC) < 80% of the predicted value and normal FEV1/FVC ratios. Multivariate logistic regression analysis was used to determine the independent risk factors for RLD. Results: RLD was identified in 34.2% (n=154) of the participants. Multivariate analysis revealed that prolonged duration of diabetes (OR = 1.15, 95% CI: 1.08-1.22, p < 0.001), poor glycemic control (HbA1c > 8.0%) (OR = 2.45, 95% CI: 1.55-3.88, p < 0.001), presence of diabetic nephropathy (OR = 2.10, 95% CI: 1.25-3.52, p = 0.004), and increased body mass index (OR = 1.08, 95% CI: 1.02-1.14, p = 0.008) were independent predictors of RLD. Conclusions: Restrictive lung dysfunctions is common among patients with T2DM. Significant independent risk factors include poor glycemic control, long duration of diabetes, diabetic nephropathy, and obesity. Lung function screening should be routinely performed in T2DM patients, particularly those with long duration of diabetes and microvascular complications as a part of their comprehensive management.